2003
DOI: 10.1097/01.ccm.0000074718.04034.bf
|View full text |Cite
|
Sign up to set email alerts
|

Fenoldopam—but not dopamine—selectively increases gastric mucosal oxygenation in dogs

Abstract: Fenoldopam dose-dependently increased microvascular oxygenation of the gastric mucosa without changing systemic oxygen transport, i.e., this drug acted selectively on the splanchnic mucosa. The increase in gastric mucosal oxygenation was mediated by DA(1)-receptors. In contrast, dopamine markedly increased systemic oxygen transport, but did not affect microvascular oxygenation of gastric mucosa. This lacking effect on gastric mucosal oxygenation was not caused by alpha(1)-mediated vasoconstriction. The regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…Moreover in the TEA study [ 15 ] , contrasting our results in earlier studies [ 9,[12][13][14] , restoring preload and thus DO 2 suffi ced to restore splanchnic oxygenation.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Moreover in the TEA study [ 15 ] , contrasting our results in earlier studies [ 9,[12][13][14] , restoring preload and thus DO 2 suffi ced to restore splanchnic oxygenation.…”
Section: Discussioncontrasting
confidence: 85%
“…The combined effect of both measures resulted in an increase in m HbO 2 even at low doses of dopamine [ 13 ] . This is in full accordance with our study on the selective dopamine receptor agonist fenoldopam, which preferentially increased m HbO 2 [ 14 ] . Additional measurements with a selective DA 1 -receptor antagonist confi rmed our hypothesis that the DA 1 -receptor is responsible for the benefi cial effects of fenoldopam.…”
Section: Modulation Of Splanchnic-catecholamine Receptor Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…In this context, dopamine has been used commonly, but its effectiveness has been questioned increasingly (6 -8). Recently, we reported that the synthetic dopaminergics dopexamine and fenoldopam increase gastric mucosal oxygenation under physiologic conditions (9,10). However, catecholamines may elicit different effects under compromised cardiocirculatory conditions, for example, hemorrhage or endotoxemia (7).…”
mentioning
confidence: 99%